AKTIVITAS JASA PEMASANGAN KAWAT GIGI (Studi Kasus Terhadap Penyedia Jasa Pemasangan Kawat Gigi Di Kelurahan Simpang Tiga Kecamatan Bukit Raya) - Annisa Marsela; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is motivated by the problems in many emerging areas of practice mounting braces illegally because it did not have permission from related institutions on the establishment of this office and the personnel who handle was not derived from the experts that dentist and orthodontic specialist. The price offered was very cheap in comparison to prices offered by dentists so as to make people more interested in coming to this place compared to the dentist. Seeing the enormous interest in the communities terhapat existence of this practice makes the existence of such practices have sprung up everywhere. The purpose of this penelitaian to know how the business activities and the mounting braces to know the advantages and disadvantages derived from running this business. This study used qualitative research methods. The selected research locations are in Keluraahan Simpang Tiga subdistrict Bukit rayaKota Pekanbaru. This study determines the main subject amounted to 7 people. Data collection techniques, among others, the method of observation and interviews as well as dokumentasi.Adapun results of research on the business activities of the installation of these braces is the installation of braces illegal activity in the district of Bukit Raya has been running from 2010 and mushroomed across the region due to numerous requests from the public (consumers ) will be the installation of braces. Installation of braces illegal conducted by business owners with self-taught skills mempuni without harm consumers in terms of health and very dangerous for the health of your teeth and mouth. Therefore, for Pekanbaru City Health Department in order to curb illegal businesses braces installation operating in Bukit Raya subdistrict and other environment sub-kecaatan Pekanbaru. And expected business owners illegal installation of braces in order to obtain a business license and provide physician practices Orthodontist in order not to harm consumers.Keywords : Illegal, Orthodontist